Hoag's object: the quintessential ring galaxy. (5th March 2015) - Brosch, Noah; Finkelman, Ido; Moiseev, Alexei
Abstract: We present new observations of Hoag's Object, known as "the most perfect ring galaxy, " that show that a preferred explanation for this object is (a) the formation of a triaxial elliptical galaxy some 10 Gyr ago, (b) the accretion of a large disk of neutral hydrogen at about the same time, (c) low-level star formation in the HI disk for all the time since that event triggered by the triaxial potential of the core.